Pengaruh Free Cash Flow Dan Leverage Terhadap Manajemen Laba Dengan Corporate Governance Sebagai Variebel Moderasi - Ria Hartati (Journal Of Communication Education, 2018)
ABSTRACT-This study aims to influence free cash flow and leverage to earning management and to abilityanalyze corporate governance as moserating variable. This sample in research is manufacturing listed inIndonesia stock exchange, use purposive sampling during years 2011-2014. In this research that were onevariable dependent, two variabel independent and four variabel moderating. Dependent variable is earningmanagement, independent variable is free cash flow and leverage. Moderating variable in this study consist ofinstitusional ownership, manajerial ownership, quality audits and independent board. The result showed thatfree cash flowhad negative significant influence on earning management. But leverage not significantlyinfluence on earning management. Moderating variable that influence the relationship of free cash flow toearning management is institusional ownership, manajerial ownership, quality audits and independent board.Meanwhile moderating variable leverage not influence the relationship to earning management. Institusionalownership, managerial ownership and independent board is not variable moderating.Keywords: Free cash flow, Leverage, Earning Management, Institusional ownership, managerial ownership,audits quality and independent board.